MATERNAL HYPERGLYCEMIA AND OVERNUTRION: EFFECTS ON MATERNAL CARE AND OFFSPRING DEVELOPMENT AND BEHAVIOR ACROSS LIFE - Martins, Marina Galleazzo (2021)
The present study evaluated if snack intake during pregnancy and lactation could aggravate previously established maternal hyperglycemia and its consequences to maternal care, as well as offspring development, metabolism, and behavior throughout life. Our hypothesis was that snack intake during pregnancy and lactation would trigger further impairments in maternal glycemia homeostasis, resulting in changes in maternal behavior as well on offspring development, metabolism, and behavior from birth to senescence. Chapter 1 describes how snack intake altered maternal food intake and decreased glucose tolerance in STZ-treated females. Birth weight classification was normalized in the offspring from hyperglycemic dams with access to snacks, which showed a patter similar to Control offspring. Moreover, hyperglycemic dams with access to snack were less anxious and had higher maternal motivation. Chapter 2 describes short and long-term consequences of this altered maternal nutrition and metabolism to both male and female offspring, analyzing glucose metabolism, behavior, and morphometric aspects in adolescence, adulthood, and senescence. Male offspring reproductive function was impaired in adulthood, while there was an increase in anxiety-like behavior in senescence, showing that consequences may only be evident in the long-term. No further compromises on offspring metabolism were observed. In conclusion, the present study showed that snack intake during pregnancy and lactation further impaired maternal hyperglycemia, leading to disruptions on maternal motivation during lactation and reduced the incidence of macrosomia in their offspring. In adulthood, the reproductive function was disrupted, and senescent offspring showed changes on anxiety-like behavior. Future studies will describe effects on offspring learning and memory, and its possible neural substrates. The experimental model used in this study is useful to study the consequences of maternal diabetes associated with inappropriate nutrition, since the glycemic levels resemble those most observed in pregnant women diagnosed with clinical or gestational diabetes. Although snack intake aggravated the glucose intolerance of mild hyperglycemic rats, glycemic levels were still within the mild range, which might explain why this condition did not lead to major impairments for both mother and offspring. However, even this mild maternal condition was enough to change maternal and offspring outcomes, reinforcing the importance of women sustaining target glucose levels and a healthy diet during pregnancy and lactation